Decolonizing Psalm 91 in an African perspective with special reference to the culture of the Yoruba people of Nigeria - Adamo, David Tuesday 1949- (2012)
This article is an attempt to reread Ps 91 in an African context using the culture of the Yoruba people of Nigeria as a point of reference. It briefly reviews certain Western methods ofinterpreting the book of Psalms which are referred to as Eurocentric. This Eurocentric interpretation, although it shares some good things with Africentric interpretation, does not adequatelymeet the everyday social, physical and spiritual aspirations of the African people. An Africentric interpretation of the Bible is an interpretation of the Bible in the light of African culture.In this article Psalm 91 is interpreted in the light of protection, healing and success which are the greatest needs in Africa.